Options for the Nigeria electricity tariff review: cost or service reflective tariff? (2020)
The improvement in the Nigerian electricity value chain has not been visible after seven years of partial privatization of the sector as the government continues to subsidize tariffs to avert the total collapse of the sector. The electricity distribution companies tagged the weak link in the value chain, have been challenged with inherited dilapidated infrastructure and poor revenue generation. The Nigeria Electricity Supply Industry is currently considering service reflective tariff options after her inability to implement a cost-reflective tariff in the sector since privatization in 2013. The electricity value chain is presently challenged with poor cash flow due to customer payment apathy, perceived corruption in the system, unavailability of a cost-reflective tariff which resulted in poor remittance to the value chain by the distribution companies. This paper reviews the power sector evolution and the reforms in the sector, the performance of Nigeria Electricity Regulatory Commission regulations, the concepts of the cost, and service reflective tariff. The paper recommends a cost-reflective tariff option with strict regulatory performance monitoring of all the value chain participants in the sector.